E-229 Aneurysm recurrence in anterior communicating artery aneurysms treated with hydrogel coated coils compared to bare metal coils. (4th August 2020) - MacDonell, J; Field, N; Entezami, P; Boulos, A; Dalfino, J; Paul, A
Abstract : Introduction/Purpose: Anterior communicating artery aneurysms (ACoAAs) account for 30 to 37% of all intracranial aneurysms and are additionally the most common location of subarachnoid hemorrhages (SAH). 1 2 Endovascular coiling has been shown to be a safe treatment option for patients with intracranial aneurysms but there remains concern regarding potentially higher recurrence and subsequently higher retreatment rates. Preliminary results from the hydrogel endovascular aneurysm treatment (HEAT) trial have demonstrated reduced recurrence rates in aneurysms treated with hydrogel coated coils. Hydrogel coated coils result in higher mean packing density however their effects on recurrence rates have yet to be elucidated. In this study we compare recurrence and retreatment rates in ACoAAs treated with hydrogel coated coils to those treated with bare metal coils. Materials and Methods: A retrospective chart review was done on all patients >18 years old with an ACoAA treated with endovascular coiling between 2014 and 2018. Follow up imaging included either magnetic resonance angiography (MRA) or cerebral angiography. Aneurysm recurrence was defined as any progress on the Raymond aneurysm occlusion scale on post-operative imaging. Treatment groups were divided into hydrogel coated coil or bare metal coil. Patients were categorized as hydrogel coated coil when ≥70% of the coil length was hydrogel coated. Patients with <70% hydrogel coated coils were placed in the bare metal coil treatment group. Fisher exact test was used to determine statistical significance. Results: 84 ACOAA were treated with coil embolization between 2014 and 2018. Post-operative imaging was available for 68 patients. 26 patients were categorized into the hydrogel treatment group and 42 into the bare metal treatment group. Of the 68 patients, 50 (74%) presented with aneurysm rupture. Sixty five percent (17/26) of patients in the hydrogel group and 79% (33/42) patients in the bare metal group presented with subarachnoid hemorrhage (p=0.26). Aneurysm recurrence was seen in 7.7% (2/26) of patients treated with hydrogel coated coils compared to 33.3% (14/42) of those treated with bare metal coils (p 0.03) (table 1). Sub-analysis of patients presenting with aneurysm rupture revealed decrease recurrence rates in patients treated with hydrogel coated coils at 5.9% (1/17) compared to patients treated with bare metal coils at 39.4% (13/33) (p 0.01). Conclusion: Hydrogel coated coils may reduce recurrence rates in the treatment of both ruptured and unruptured ACoAAs. References: Cai W., et al., Anterior communicating artery aneurysm morphology and the risk of rupture. World Neurosurg 2018;109:119–126 Dehdashti AR, Chiluwal AK, Regli L. The implication of anterior communicating complex rotation and 3-dimensional computerized tomography angiography findings in surgical approach to anterior communicating artery aneurysms. World Neurosurg 2016;91:34–42. Disclosures: J. MacDonell: None. N. Field: None. P. Entezami: None. A. Boulos: None. J. Dalfino: None. A. Paul: None.